Instructional Design for virtual worlds: Basic principles for learning environments - Nadine Ojstersek; Michael Kerres (Looking Toward the Future of Technology-Enhanced Education: Ubiquitous Learning and the Digital Native, 2010)
This paper gives an overview of the didactic elements relevant to learning opportunities in virtual worlds. Moreover, the specific requirements of virtual worlds are investigated in more detail using the C3-model of didactic components. Following this model, the specifications of virtual worlds are illustrated with regard to components content, communication and construction. The use of virtual worlds is often connected with the hope for stronger immersion, which is encouraged by the possibility of three-dimensionality and the representation of the learner by a virtual representative. However, learning-/teaching processes are not automatically improved by the use of virtual worlds. The possibilities offered by potential virtual worlds can only be honoured when a dedicated didactical concept is carried out. This means a complex composition process which has to take the specific features of virtual worlds into consideration.